ISOLASI DAN ANALISIS KUALITAS DNA PLASMID (pGEM®-3Zf(+)) SEBAGAI SEDIAAN KEBUTUHAN PRAKTIKUM DI LAB. BIOLOGI FST - Arifah Khusnuryani; Jumailatus Solihah; Anif Yuni Muallifah (Integrated Lab Journal, 2016)
Implementation of practical work in biology laboratory needs supporting media including laboratory equipments and materials. In genetics and molecular biology, the routine materials are mostly molecular resources, which are produced by certain company. To get the materials, we must order and pay for a relative high price.These molecular resources in biology laboratory is not only beneficial for practical activity, but also useful for research activity in related fields.This research works as an application of methods applied in laboratory to result in a product that is valuable in practical works, i.e. the pGEM plasmids. The methods that were employed involved the transformation of E. coli with pGEM plasmid, blue-white screening by using X-gal, and plasmid isolation by alkaline lysis method. The transformation results showed a relative low efficiency at 1,2 x 103cfu/µg DNA. The electrophoresis in 0.8% agarose gel demonstrated that the plasmid DNA was successfully isolated with some thin bands at position 3000-4000bp, despite of a large chromosomal DNA and some smear RNA were still observed. The DNA obtained is pure enough, characterized by the ratio of A260/280 at the range of 1,8-2,0.